Warming and marine heatwaves tropicalize rocky reefs communities in the Gulf of California. (August 2022) - Favoretto, Fabio; Sánchez, Carlos; Aburto-Oropeza, Octavio
Highlights: The rocky reefs in the Gulf of California are important biodiversity hotspots. Rocky reefs warmed 1 °C on average since 1982 and marine heatwaves increased 3-fold. Fish and invertebrates were affected by these warming events. Rocky reefs tropicalized as species with warm water affinities increased northward. Long-term consequences of this reconfiguration are yet to be determined. Abstract: Globally, marine communities are experiencing gradual warming and extreme heatwaves causing species to shift in geographic range. As a result, the biological assemblages outside tropical latitudes are being reorganized or "tropicalized" as warm-affinity species become increasingly dominant and cool water species recede, with impacts on our economies, food supply, and health. In the Gulf of California, existing oceanographic discontinuities shape marine communities by creating different assemblages according to environmental affinities. In this study, we show how a known ecological boundary underwent a northward shift of 1.5° latitude because of an average 1 °C gradual warming over the last decade (2010–2020) and extreme marine heatwaves threefold more frequent. Such shift homogenized environmental conditions and reconfigured rocky reefs communities. Fish biomass decreased of 43%, whereas invertebrates, which recorded a 35% decrease in overall abundance, showed different community configurations depending on the climate regime. Stony coral species with warm water affinities increased with a reduction of cold-water species during the last El Niño. The long-term consequences of the tropicalization of these rocky reefs' communities are still uncertain. This study underlines the importance of long-term monitoring of key habitats to quantify, predict, and adapt to future climatic stresses.